War and peace in totalitarian regimes according to the philosopher Hanna Arendt - Khaleel, Refka; Majhoul, Faisal (Al-Adab Journal, 2023)
Hanna Arendt tried to explain what totalitarian regimes are, and how war seeps into and relies on it to spread terror and the control of governments over peoples through it, as nations become oppressed, absent and far from reality. Totalitarian regimes have the task of control and terror to ensure their continued existence. There is no place left for peace to be achieved except through the pursuit of freedom and healthy and genuine communication among all. Totalitarian regimes have no meaning of peace, as they turn individuals into masses and strip them of their individual existence into isolated victims through terrorism and violence. The goal of totalitarianism is to eliminate human action, so that freedoms disappear and authoritarianism prevails to impose power and control. All evil is a trivial and very ordinary act. For Hanna Arendt, the path to peace is to create an oasis or a cultural-intellectual world, in which we communicate with ourselves and our subjects freely, an oasis in which an active and productive life, a new life with a new politics.